Chapter 1. Commercial Vegetable Production in Florida: VPH ch. 1, CV100/HS710, rev. 6/2024 - Agehara, Shinsuke; Dufault, Nicholas S.; Kanissery, Ramdas; Martini, Xavier (EDIS, 2024)
Chapter 1 of the Vegetable Production Handbook of Florida